Application and Development Trend of Laser Technology in Food 3D Printing - TONG Qiang, XIAO Shuailei, JIANG Yu, DONG Xiuping, PANG Guibing (Shipin Kexue)
With the rapid development of food 3D printing technology, its innovative combined application with various auxiliary technologies is attracting more and more attention. Laser technology is characterized by high precision, high energy and rapid material shaping, which matches highly with the personalized customization advantage of food 3D printing technology. The combination of these two techniques shows great application prospects in the field of food processing. This article begins with an introduction to the current development of food 3D printing technology and laser technology, and focuses on the application of laser technology in food 3D printing from the perspectives of laser parameters (such as wavelength, power and pulse) and processing advantages. At the same time, this article points out the challenges facing the application of laser technology in food 3D printing, such as food safety and application limitations. Finally, this article summarizes trends in the deep integration of laser technology and food 3D printing technology and points out future directions so as to provide a theoretical basis for the innovative application of laser technology in the field of food 3D printing.